The Development Of Islamic Liberal And Its Impact On Muslim In Malaysia - Nur Bakri Abd Hamid; Naufal Ahmad Rijalul Alam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Liberal Islamic thought has begun to take root and grow firmly in Malaysia since the era of colonialism, especially British colonialism since the 18th century. The Liberal Islamic narrative occurs when Muslims have an ideology of liberalism. The distribution of studies includes various disciplines: the development of liberalism, its effects in Malaysia, and preaching strategies to curb its contagion. This study focuses on the history of the development of liberalism in general and Liberal Islam in principle as well as its implications and solutions. This study is a qualitative study and through content analysis from related books and articles. From the results of this study, the researcher found that Liberal Islam has spread into the ideology of the Malaysian Muslim community because of a lack of understanding of Islam as a whole and a desire for progress and progressiveness. This also stems from the community's desire to see Islam as simple and accommodating to all community issues. They think Islam is a rational religion, not one that refers to the authentic texts, the Quran and the Sunnah.